2007
DOI: 10.1037/0278-7393.33.3.615
|View full text |Cite
|
Sign up to set email alerts
|

Working memory, attention control, and the n-back task: A question of construct validity.

Abstract: The N-back task requires participants to decide whether each stimulus in a sequence matches the one that appeared n items ago. Although N-back has become a standard "executive" working memory (WM) measure in cognitive neuroscience, it has been subjected to few behavioral tests of construct validity. A combined experimental- correlational study tested the attention-control demands of verbal 2- and 3-back tasks by presenting n = 1 "lure" foils. Lures elicited more false alarms than control foils in both 2- and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
621
4
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(652 citation statements)
references
References 42 publications
22
621
4
5
Order By: Relevance
“…Comparisons of age groups showed stronger interference effects for lure items in the older group, with a clear temporal decay, paired with facilitation for targets. These results are in line with those of earlier studies that demonstrated interference effects on accuracy for lures with relatively short lags (Gray et al, 2003;Kane et al, 2007;Oberauer, 2005;Perlstein et al, 2004). Furthermore, our n-back data also show, for the first time, facilitation for targets relative to nontargets among older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Comparisons of age groups showed stronger interference effects for lure items in the older group, with a clear temporal decay, paired with facilitation for targets. These results are in line with those of earlier studies that demonstrated interference effects on accuracy for lures with relatively short lags (Gray et al, 2003;Kane et al, 2007;Oberauer, 2005;Perlstein et al, 2004). Furthermore, our n-back data also show, for the first time, facilitation for targets relative to nontargets among older adults.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies that have examined the convergent validity between the N-back task and other WM measures, such as the operation span task (OSPAN), show correlations with lower WM loads (Shelton et al, 2007) and varied results with the 3-back condition (Shelton et al, 2007;Kane et al, 2007). Such studies suggest that at higher WM loads, attentional components and/or short-term memory processes may be measured rather than WM capacity exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…This task consisted of a series of stimuli (spoken consonants) that were sequentially played at an interstimulus interval of two seconds [22]. For each stimulus, the participant was instructed to respond as quickly and accurately as possible if it was a target.…”
Section: Methodsmentioning
confidence: 99%